Oestrous sheep serum balances ROS levels to supply in vitro capacitation of ram spermatozoa - Del Olmo, E; García-Álvarez, O; Maroto-Morales, A; Ramón, M; Iniesta-Cuerda, M; Martinez-Pastor, F; Montoro, V; Soler, A J; Garde, J J; Fernández-Santos, M R (Reproduction in domestic animals, 2016)
Reactive oxygen species (ROS) are fundamental for intracellular signalling. In spermatozoa, they are involved both to apoptosis and to capacitation, and changes in ROS levels can alter the balance between these two processes. Oestrous sheep serum (OSS) is considered an efficient agent for in vitro capacitation of ram spermatozoa. We have explored the effects of OSS on ram sperm physiology, especially on ROS production, during in vitro capacitation. Semen samples from 15 rams were cryopreserved. After thawing, samples were submitted to four treatments: control (CTL), 10% OSS supplementation for in vitro sperm capacitation, caspase inhibitor (INH, Z-VAD-FMK 100 μM) and OSS (10%) plus caspase inhibitor (I + E). Sperm samples were incubated for 30 min at 38.5°C and 5% CO2 and evaluated motility and kinetic parameters by computer-assisted semen analysis (CASA) and viability (propidium iodide), apoptotic-like membrane changes (YO-PRO-1), acrosomal status (PNA-FITC), intracellular calcium (FLUO-3), membrane fluidity (M540) and ROS production (CM-H2 DCFDA) by flow cytometry. OSS induced changes in kinetic parameters compatible with capacitation, with a decrease in the percentage of progressive motility and linearity, and an increase in the amplitude of the lateral displacement of the sperm head (p < .05). Moreover, OSS increased the proportion of M540+ viable spermatozoa, YO-PRO-1+ and acrosome-reacted spermatozoa (p < .05). After incubation, OSS and I+E achieved lower ROS levels (p < .05). Ca(2+) levels did not change with the incubation, but were slightly higher (p < .05) when both OSS and the inhibitor were present. We suggest that OSS may modulate ROS levels, allowing intracellular signalling for capacitation to occur while preventing higher levels that could trigger apoptosis.
Keywords: Animals; Female; Caspases; spermie; kapacitace spermií; ženské pohlaví; Spermatozoa; ovce; Reactive Oxygen Species; estrus; motilita spermií; Male; Sheep; Estrus; reaktivní formy kyslíku; Sperm Capacitation; Sperm Motility; mužské pohlaví; kaspasy; zvířata